2010
DOI: 10.1111/j.1745-4557.2009.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties and Fruit Quality During Long‐term Storage of “Rocha” Pear: Effects of Maturity and Storage Conditions

Abstract: Free radical scavenging activity and the content of ascorbic acid and glutathione were investigated during long‐term storage of the pear (Pyrus communis L. ‘Rocha’) fruit harvested at different maturity stages, stored in air or under controlled atmosphere and subjected to postharvest treatments with diphenylamine (DPA) and 1‐methylcyclopropene (1‐MCP). Harvest maturity had a significant effect on storage disorders, fruit firmness, soluble solids content and acidity. Differences in ascorbate content and free ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 43 publications
4
42
0
2
Order By: Relevance
“…Silva et al (2010) reported no effect of 1-MCP at 500 nl l À1 on acidity of ''Rocha'' pear stored at 0 C for up to eight months in relation to untreated controls, but fruit treated with 500 or 1000 nl l À1 of 1-MCP had higher acidity after a four-month storage period than fruit treated with 100 nl l À1 of 1-MCP or Food Science and Technology International 0(0) untreated controls (Isidoro and Almeida, 2006). The effect of 1-MCP on titratable acidity may be dependent on the maturity of the fruit at harvest, as suggested by the results reported by Alpalha˜o et al (2008) in two consecutive years: higher titratable in 1-MCP-treated fruit in relation to untreated controls during storage and shelf life were registered in one year, but no differences were observed in another year.…”
Section: Changes In Titratable Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al (2010) reported no effect of 1-MCP at 500 nl l À1 on acidity of ''Rocha'' pear stored at 0 C for up to eight months in relation to untreated controls, but fruit treated with 500 or 1000 nl l À1 of 1-MCP had higher acidity after a four-month storage period than fruit treated with 100 nl l À1 of 1-MCP or Food Science and Technology International 0(0) untreated controls (Isidoro and Almeida, 2006). The effect of 1-MCP on titratable acidity may be dependent on the maturity of the fruit at harvest, as suggested by the results reported by Alpalha˜o et al (2008) in two consecutive years: higher titratable in 1-MCP-treated fruit in relation to untreated controls during storage and shelf life were registered in one year, but no differences were observed in another year.…”
Section: Changes In Titratable Aciditymentioning
confidence: 99%
“…The ethylene action inhibitor 1-methylcyclopropene (1-MCP) reduces or prevents superficial scald in pear cultivars (Argenta et al, 2003;Chiriboga et al, 2013;Ekman et al, 2004;Isidoro and Almeida, 2006;Silva et al, 2010;Trinchero et al, 2004;Villalobos-Acun˜a et al, 2011;Xie et al, 2014). A few studies have been conducted to evaluate 1-MCP effects on ''Rocha'' pear at the laboratory scale and in packinghouse settings (Alpalha˜o et al, 2008;Almeida, 2006, 2008;Silva et al, 2008Silva et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the balance between the content of oxidative species and antioxidants within the fruit skin has an important role in the development and progression of superficial scald in both apples and pears (Ju et al, 1996;Rao et al, 1998;Diamantidis et al, 2002;Zubini et al, 2007;Whitaker et al, 2009;Silva et al, 2010). Low temperature storage weakens the antioxidant mechanisms of plant tissues (Mir et al, 1999) including pears (Chiriboga et al, 2013) hence making the fruit more prone to develop this physiological disorder.…”
Section: Introductionmentioning
confidence: 99%
“…‘Rocha’ pear can be stored for up to 10 months under controlled atmosphere (CA) (2.5–3 kPa O 2 + 0.5–0.7 kPa CO 2 ) . However, during long‐term storage under CA, similarly to other pear cultivars, it develops two major physiological disorders: internal browning and superficial scald . Internal browning disorders (IBD) affect the inner part of the fruit and in the most severe cases the damage can be extended up to the peel…”
Section: Introductionmentioning
confidence: 98%
“…1 However, during long-term storage under CA, similarly to other pear cultivars, it develops two major physiological disorders: internal browning and superficial scald. 2 Internal browning disorders (IBD) affect the inner part of the fruit and in the most severe cases the damage can be extended up to the peel. 3 IBD results from the reaction of polyphenoloxidase (PPO) with its phenolic substrates, leading to the formation of o-quinones which spontaneously polymerize to form melanins, the browning compounds.…”
Section: Introductionmentioning
confidence: 99%